A transient mitochondrial switch underlies long lasting effects of adolescent cannabis - Christina Ioannidou; Irene Manzanares-Sierra; Daniel Jimenez-Blasco; Darío García-Rodriguez; Israel Manjarrés-Raza; Francisca Julio-Kalajzić; Antonio C. Pagano Zottola; Martina Di Bartolomeo; Guillaume Ferreira; Juan P. Bolaños; Giovanni Marsicano; Arnau Busquets-Garcia (Neuropsychopharmacology, 2026)
Abstract Adolescent cannabis use produces lasting and sex-specific effects into adulthood, although poorly explained mechanistically. This study links these cannabis-induced effects to sex-dependent changes in phosphorylation of mitochondrial Complex I subunit NDUFS4 during adolescence, identifying mitochondrial pathways as causal mechanisms and potential therapeutic targets to reduce their long-term consequences.